2020
DOI: 10.1177/1534735420975861
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Natural Therapies Potentially Relevant in Triple Negative Breast Cancer Aimed at Targeting Cancer Cell Vulnerabilities

Abstract: We reviewed the research into the mechanisms of growth of triple negative breast cancer (TNBC) based on laboratory pre-clinical studies that have shaped understanding of the disease over the past decade. In response to these findings, we propose an approach to potentially prevent cancer metabolic adaptation and recurrence. This paper collates pre-clinical results, first to determine the tumor’s mechanisms of growth and then to source natural substances that could potentially suppress those mechanisms. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 112 publications
0
29
0
Order By: Relevance
“…14 , we can see that most significant pathway among top 20 ranking pathways for BLCA, BRCA, COAD and HNSC is “pathways in cancer”, demonstrating that the predicted driver genes with our PDGPCS are significantly related with cancers. We also identified other cancer-related pathways for BLCA, BRCA, COAD and HNSC, such as “PI3K-Akt signaling pathway” [ 23 ] and “ErbB signaling pathway” [ 24 ] for BLCA, “MAPK signaling pathway” [ 25 ] and “Jak-STAT signaling pathway” [ 26 ] for BRCA, “Rap1 signaling pathway” [ 27 ] for COAD, and “VEGF signaling pathway” for HNSC [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…14 , we can see that most significant pathway among top 20 ranking pathways for BLCA, BRCA, COAD and HNSC is “pathways in cancer”, demonstrating that the predicted driver genes with our PDGPCS are significantly related with cancers. We also identified other cancer-related pathways for BLCA, BRCA, COAD and HNSC, such as “PI3K-Akt signaling pathway” [ 23 ] and “ErbB signaling pathway” [ 24 ] for BLCA, “MAPK signaling pathway” [ 25 ] and “Jak-STAT signaling pathway” [ 26 ] for BRCA, “Rap1 signaling pathway” [ 27 ] for COAD, and “VEGF signaling pathway” for HNSC [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…There are many compounds of plants (such as Allium spp., Glycine spp., Curcuma longa and Panax ginseng) that can inhibit triple negative breast cancer through the specific pathway including HIF-I, MAPK, MTAP, NF-B, PI3K, p53 and STAT3. The inhibition of these pathways causes inhibition of tumor growth and induction of apoptosis (Webb and Kukard, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells can adapt and change their mechanism of action to use biochemical pathways that are unaffected by usual pharmaceutical therapies. While chemotherapy is one of the most effective cancer therapies, some tumor cells are resistant to this treatment (Webb & Kukard, 2020). Breast cancer (BC) is the second most usually diagnosed cancer type and the second most common cause of cancer death, up to 15% of women in the United States, after lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy and radiotherapy are the typically used treatment for TNBC, but it has been found that these cells are resistant to these treatments. The overall survival with TNBC is lower than in other types of BC (Knickle et al, 2018; Webb & Kukard, 2020). The comparison of receptors between normal breast cancer cells and TNBC cells (Damaskos et al, 2021) is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation